Flow past a near-wall retrograde rotating cylinder at varying rotation and gap ratios - Tan, Soon Keat (2019)
The flow past a circular cylinder that is rotating retrograde near a turbulent wall boundary layer at Re = 10 000 has been investigated experimentally using particle image velocimetry (PIV). The cylinder rotates in retrograde direction with different rotation ratios from α = 0 to 2, where α is defined as the ratio of the peripheral speed on the cylinder surface divided by the free-stream velocity. The gap ratio, G * = G/D, is varied between 0 and 1.6, where G is the gap between the cylinder and the plane wall, and D is the cylinder diameter. The flow structure is greatly modified due to the influence of wall proximity and cylinder rotation, notably the onset/suppression, frequency and strength of vortex shedding. Similar to a near-wall stationary cylinder, there exists a critical gap ratio (about 0.4) below which periodic vortex shedding from the cylinder is suppressed. On the other hand, the cylinder rotation causes vortex shedding to cease at α ≥ 1.6, which is slightly lower than the reported value of α ≈ 2 in the literature on rotating cylinder in uniform flow. However, reducing G * and increasing α do not always favor the suppression of vortex shedding. In fact, cylinder rotation promotes vortex shedding over a certain range (α < 1). As α increases, the length of recirculation region behind the cylinder, which is indicated by the movement of the mean saddle point, decreases almost linearly. The effects of wall proximity and cylinder rotation are also evident on the ensemble-averaged flow field, such as the turbulent kinetic energy and Reynolds shear stress.